Lost on the Amazon - Montgomery, R. A.; Millet, Jason (Waitsfield, Vt. : Chooseco, 2005)
Asks the reader to choose the plot path in a story in which most of a medical team researching tropical diseases goes missing in the Amazon jungle, leaving a young doctor--the reader--alone.
Revised version of 1983 publication published by Bantam.
4.0
3-6.
3-6
Keywords: Adventure and adventurers -- Juvenile fiction; Adventure and adventurers -- Fiction; Plot-your-own stories; Adventure fiction; Plot-your-own stories; Amazon River Region -- Juvenile fiction; Amazon River Region -- Fiction; Amazon River Region -- Fiction; Adventure fiction; Plot-your-own stories